NON-EQUIVALENT VOCABULARY OF THE RUSSIAN AND UZBEK LANGUAGE - Khanova Dilrabo Baratovna (Galaxy International Interdisciplinary Research Journal, 2022)
Non-equivalent vocabulary is studied as one of the factors that change the norms of the Uzbek literary language. A general description of the language situation in modern Uzbekistan is given against the background of the informatization of society and the process of integrating languages ​​and cultures. Based on the analysis of cases of the use of non-equivalent vocabulary in oral and written speech, the author states its significant influence on the process of democratization of the literary norm.